Gun-shy: Refusal to answer questions about firearm ownership. Issue 2 (1st June 2019) - Urbatsch, R.
Abstract: In recent years, surveys in the United States have faced increasing refusal to answer questions about firearm ownership, even as other similar questions see no comparable up-tick in item nonresponse. Asymmetrical polarization, elite messaging, and changing media institutions all suggest that the surging nonresponse concerning gun-ownership questions may be increasingly concentrated among those with rightward political and partisan leanings, potentially skewing inferences about gun-related issues. Data from the General Social Survey confirms that the increase in probability of declining to answer firearm-ownership questions is particularly stark among those identifying as Republicans, particularly those with a conservative outlook skeptical of government.